(untitled) (De Musica, 2021)
The articles collected in the present issue of De Musica derive from contributions to the international conference “Penser la musique à l’ère du web / Thinking Music in the Web Age” and continue the investigation developed in the previous issue on the rapid and profound transformations of the contemporary musical culture in the web age. They deal in particular with the impact of the so-called digital revolution on the production, the distribution and the reception of music.